The Role of Arabic Language Learning in Supporting the Ability to Memorize the Quran - Tareq Alsokari; Samiullah Adel; Afifah Salsabila Defri (Journal of Arabic Literature, Teaching and Learning, 2026)
The Arabic language is intrinsically linked to the Quran, as the Quran is written in Arabic; therefore, those who understand Arabic can easily grasp the content and meaning of the Quran. This study aims to examine the influence of the Arabic language on the process of memorizing the Quran, thereby demonstrating the role of Arabic in Quranic memorization. This study employs a qualitative method with a literature review approach to analyze, synthesize, and summarize the results of relevant studies in a descriptive manner. The findings indicate that there are four (4) roles of Arabic language learning in supporting Quranic proficiency, namely: i) Facilitating the memorization of the Quran; ii) Expanding vocabulary iii) understanding the values contained in the Quran iv). Enhancing understanding of Quranic verses. The implementation of this study demonstrates that the role of the Arabic language in memorizing the Quran is closely linked to significant improvements in the memorization process, motivation, and a deeper understanding of the Quranic text.